Retrospective study of treatment patterns and outcomes post‐lenalidomide for multiple myeloma in Canada. (27th June 2021) - Reece, Donna E.; Masih‐Khan, Esther; Atenafu, Ehetu G.; Jimenez‐Zepeda, Victor H.; McCurdy, Arleigh; Song, Kevin; LeBlanc, Richard; Sebag, Michael; White, Darrell; Cherniawsky, Hannah; Reiman, Anthony; Stakiw, Julie; et al.
Abstract: Lenalidomide is an important component of initial therapy in newly diagnosed multiple myeloma, either as maintenance therapy post‐autologous stem cell transplantation (ASCT) or as first‐line therapy with dexamethasone for patients' ineligible for ASCT (non‐ASCT). This retrospective study investigated treatment patterns and outcomes for ASCT‐eligible and ‐ineligible patients who relapsed after lenalidomide as part of first‐line therapy, based on data from the Canadian Myeloma Research Group Database for patients treated between January 2007 and April 2019. Among 256 patients who progressed on lenalidomide maintenance therapy, 28.5% received further immunomodulatory derivative‐based (IMiD‐based) therapy (lenalidomide/pomalidomide) without a proteasome inhibitor (PI) (bortezomib/carfilzomib/ixazomib), 26.2% received PI‐based therapy without an IMiD, 19.5% received both an IMiD plus PI, 13.5% received daratumumab‐based regimens, and 12.1% underwent salvage ASCT. Median progression‐free survival (PFS) was longest for daratumumab‐based therapy (22.7 months) and salvage ASCT (23.4 months) and ranged from 6.6 to 7.3 months for the other treatments ( P < .0001). Median overall survival (OS) was also longest for daratumumab and salvage ASCT. A total of 87 non‐ASCT patients received subsequent therapy, with 66.7% receiving bortezomib‐based therapy and 13.8% receiving other PI‐based therapy. Median PFS was 15.4 and 24.8 months for bortezomib‐based and other PI‐based therapy, respectively ( P = .404). During most of the study period, daratumumab was not funded; in this setting, switching to a different therapeutic class following relapse on lenalidomide produced the longest remissions for non‐ASCT patients. Further prospective studies are warranted to determine optimum treatment following relapse on lenalidomide, especially in the light of increased access to daratumumab.